Nitrogen and Radiation Use Efficiency in Temperate Pastures Low Quality Soils - Correa, Natalia M. (2013)
In the humid pampa of Argentina, tall fescue is used in wet or low fertility soils whereas tall wheatgrass is used in flooded and alkaline environments (Maddaloni y Ferrari 2005). Autumn and winter growth rates are lower than in spring, and higher in tall fescue than in tall wheatgrass. In these species, maximum responses to nitrogen (N) fertilization occurs when it is done at the end of winter, but livestock farmers sometimes fertilize swards in late summer with the aim to get more forage in late autumn and winter. Due to the characteristics of the environments to which they adapt and the morphogenetic processes inherent to each species, neither direct comparison is possible, nor is the use of the same treatments. However, when farmers must decide about pasture fertilization, they should know the effectiveness of this practice in each situation. According to that, two experiments were carried out to determine the radiation use efficiency (RUE) and N utilization indexes in tall fescue and tall wheatgrass swards fertilized with N.